The Influence of Nonformal Education to The Religious Understanding on Learning Group of People in Sunday Morning Madani Community in Bojonegoro Regency - Tari Yono; Rahmat Arofah Hari Cahyadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
This study aims to explore what underlies the Influence of Non-formal Education on the understanding of religion in the congregation of early morning